What Is the Success of Implants Placed in Fibula Flap? A Systematic Review and Meta-Analysis - Pooja Gangwani; Mohammed Almana; Basir Barmak; Antonia Kolokythas (eJournal of Oral Maxillofacial Research)
Objectives: The purpose of this systematic review and meta-analysis is to examine the success rate of osseointegrated dental implants placed secondarily in fibula free flaps using the Albrektsson and colleagues criteria.